ICT-based fluorescent probes for intracellular pH and biological species detection - Wu, You; Ge, Chengyan; Zhang, Ying; Wang, Yalong; Zhang, Deteng (Frontiers in Chemistry, 2023)
Fluorescent probes, typically based on the intramolecular charge transfer (ICT) mechanism, have received considerable research attention in cell detection due to their non-invasiveness, fast response, easy regulation, high sensitivity, and low damage tolerance for in vivo bio-samples. Generally, intracellular pH and biological species such as various gases, metal ions, and anions constitute the foundation of cells and participate in the basic physiological processes, whose abnormal level can lead to poisoning, cardiovascular disease, and cancer in living organisms. Therefore, monitoring of their quantity plays an essential role in understanding the status of organisms and preventing, diagnosing, and treating diseases. In the last decades, remarkable progress has been made in developing ICT probes for the detection of biological elements. In this review, we highlight the recent ICT probes focusing primarily on the detection of intracellular pH, various gases (H2S, CO, H2O2, and NO), metal ions (Cu2+, Hg2+, Pb2+, Zn2+, and Al3+), and anions (ClO−, CN−, SO32−, and F−). In addition, we discuss the issues and limitations of ICT-based fluorescent probes for in vivo detection and explore the clinical translational potential and challenges of these materials, providing valuable guidance and insights for the design of fluorescent materials.